UNESCO 2019. Global Education Monitoring Report - Gender Report : Building bridges for gender equality (United Nations Educational, Scientific and Cultural Organization ParisFR, 2019)
This publication is enriched by analysis of the intersections between gender, education, migration and displacement. It examines the way that relations in both origin and host communities influence women's and men's experiences as migrants and refugees - and the role of education.
Keywords: UNESCO